Aligning global organizations' human capital needs and global supply‐chain strategies. (20th November 2012) - Harvey, Michael; Fisher, Ron; McPhail, Ruth; Moeller, Miriam
<x xml:space="preserve">Abstract</x> Globalization of business has had a profound impact on organizations. The focus of management has shifted from a domestic one to a more complex understanding of how to compete effectively in the global marketplace. One element that has accentuated the need for managers to develop a global mindset is in the area of global supply‐chain management. The need to modify and update the type of manager needed to manage global interorganizational relationships effectively has arrived. This theoretical research examines the growing importance of having the appropriate human resource management (HRM) processes to select, train, and retain competent global supply‐chain managers. In addressing the human resource dimensions of successful global supply‐chain management the growing importance of HRM in the management of supply chains is presented as a combination of resource‐based (e.g. internal), market‐based (e.g. external) and dynamic capabilities perspectives. In addition, selection, training and assessing the new 'breed' of global supply‐chain managers is explored.